2009
DOI: 10.1002/app.31511
|View full text |Cite
|
Sign up to set email alerts
|

Chemical formation, characterization and properties of polycarbazole

Abstract: Polycarbazole (PCz) was synthesized by chemical polymerization of carbazole in acetonitrile medium using ammonium persulfate as oxidant. The selection of solvent, concentration of the monomer, composition of the solvent, polymerization time, temperature, and pH were optimized to obtain better quality and yield of the polycarbazole. The synthesized polycarbazole was characterized by various techniques such as UV-Visible, FTIR, 1 H-NMR, 13 C-NMR, COSY, NOESY, and XRD spectroscopy. The solubility of the polycarba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 92 publications
7
35
0
Order By: Relevance
“…These results are in good agreement with the earlier reports[24]. The peaks at 590 and 744 cm -1 in the spectrum of PCz might be attributed to C=C out of plane twisting and vibrations of ring distortion of aromatic structure of PCz moiety, respectively.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…These results are in good agreement with the earlier reports[24]. The peaks at 590 and 744 cm -1 in the spectrum of PCz might be attributed to C=C out of plane twisting and vibrations of ring distortion of aromatic structure of PCz moiety, respectively.…”
supporting
confidence: 93%
“…PCz showed peaks at 21.1, 23.9, 29.4, 33.1 and 35.1 o 2θ, which is in accordance with the previously published reports[24][25]. PCz showed peaks at 21.1, 23.9, 29.4, 33.1 and 35.1 o 2θ, which is in accordance with the previously published reports[24][25].…”
supporting
confidence: 92%
“…56 The diffraction pattern of PCZ have peak at about 2y ¼ 20.1 , which is a characteristic peak of poly(carbazole). 51 The characteristic peak of PCZ has been shifted slightly to low angle in the copolymer. This shows the crystalline nature of the copolymer.…”
Section: Xrd Measurements Of the Copolymers Of Imi And Czmentioning
confidence: 98%
“…It is reported that poly (carbazole) exhibits ANHA stretching vibration 51 at 3053 cm À1 and poly(imidazole) exhibits ANHA vibration weak peak at 3077 cm À1 . Sharp band at 3052 cm À1 due to characteristic NAH stretching vibration suggests the presence of ANHA groups in IMI and CZ units.…”
Section: Ftir Spectra Of the Copolymers Of Imi And Czmentioning
confidence: 99%
“…The characteristic peaks can be identified at 3192, 1620, 1440, 1200, 825, and 700 cm − 1 . These peaks can be assigned to the N-H stretching of the heteroaromatics; the C_C stretching of the aromatic compound; the C-N stretching of substitutions; the C-H in plane bending; the C-H deformation of tri-substituted benzene; and the C-H out-of-plane bending, respectively [15,23].…”
Section: Characterization Of Pcz and Sf Hydrogelmentioning
confidence: 99%